ANALYZING THE INFLUENCE OF PRICE AND PRODUCT QUALITY ON BUYING DECISION HONDA MATIC MOTORCYLES IN MANADO - Tamunu, Melvern; Tumewu, Ferdinand (FEB Universitas Sam Ratulangi Manado, 2014)
Competition are currently make the company tight competition. Prices and product quality was a thing would influence the buying decision. This study aims to determine the influence of price and product quality on buying decision honda matic motorcyles in Manado. Where the independent variables are price, and the product quality influence the buying decision as the dependent variable. This research used quantitative method. The analytical method used was multiple linear regression analysis. The data used in this research is primary data obtain through the questionnaire. The population in this study is the owner of the Honda motorcycle. Samples are taken from 100 respondents using purposive sampling technique. The results of the study variables price and product quality variables simultaneously against influential buying decision. Companies should improve the image of Honda. Although Honda Matic affordable, but not a cheap bike, so the selling price in the market is maintained. This relates to the market assumptions regarding post-sale price of motorcycles in the market. The company should be able to maintain or even increase quality of the product. Keywords: purchase decision, price, product quality